GROWTH OF THE INDIAN SHAD, MILS A ILISHA (HAMILTON), IN THE TIDAL STRETCH OF THE HOOGHLY - Sujansingani, K H (Indian Journal of Fisheries, 2015)
The Indian shad Hilsa ilisha (Hamilton), known as " Ilish " in Bengal, is fished in the Hooghly practically throughout the year and forms an important fishery. The fish which breeds in the tidal stretch of the river, has an extended breeding season and its juveniles appear in catches in large numbers in the cold season from end of October to February-March, when Bhin-jals (conical bag-nets) are operated. This regular fishing of young Hilsa which some years back was probably confined to Nawabgunge area, about 20 miles north of Calcutta (Hora, 1938), now exists in a stretch of about 45 miles from Ulubaria to Chandernagar (about 20 miles south of Calcutta to 25 miles north of it) where Bhin-jals are found to be operating, and takes a heavy toll of the juvenile fish, growth study of which is presented in this account.